2020
DOI: 10.3390/nu12040887
|View full text |Cite
|
Sign up to set email alerts
|

Language of Health of Young Australian Adults: A Qualitative Exploration of Perceptions of Health, Wellbeing and Health Promotion via Online Conversations

Abstract: Young adults (YA) are in a critical stage of life for the encouragement of healthy behaviours such as healthy eating and exercising. This research explored Australian YA values and perceptions related to health, healthy behaviours and health promotion efforts. This qualitative analysis involved n = 166, Australian 18–24 year-olds recruited through a market research field house. Participants (63% currently studying at tertiary level) engaged in a facilitated in-depth online conversation around health and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…In parallel to these findings, our Communicating Health project has provided an understanding of the need for nuanced messaging that avoids using the rhetoric of the 'good and 'bad' approach to food and health [61] and responds to how young adults describe health [62]. Thus, future studies should track whether the implementation of the provided recommendations resulted in increased engagement metrics on their platform.…”
Section: Discussionmentioning
confidence: 91%
“…In parallel to these findings, our Communicating Health project has provided an understanding of the need for nuanced messaging that avoids using the rhetoric of the 'good and 'bad' approach to food and health [61] and responds to how young adults describe health [62]. Thus, future studies should track whether the implementation of the provided recommendations resulted in increased engagement metrics on their platform.…”
Section: Discussionmentioning
confidence: 91%
“…Although, of course, it is not known which of these comes first (the money or the choice). Our previous research has found that many young adults have limited financial resources and sometimes limited knowledge of budgeting their finances, so healthy eating is not always at the top of their priorities [38]. Scarcity of money and time have a negative impact on both physical activity and eating behaviours, including consumption of fruit and vegetables and energy-dense, nutrient-poor foods [49].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline exploration of aspects of the online conversations related to the language of health [38] found that young adults had a holistic view of health and that competing demands hindered their ability to realise healthy behaviours. Current healthy eating messaging did not address their needs.…”
mentioning
confidence: 99%
“…Communicating health messages clearly and openly to the public is challenging, as much of the evidence focuses on longevity and disease prevention, rather than behaviours that generate instant results and gratification [ 1 ]. Previous research has indicated that young adults and university students are often uninterested in the long-term benefits or consequences of their current eating behaviours [ 2 , 3 ]. Whilst nutrition science has enabled countless discoveries and progressions in science [ 4 ], nutrition science is more complicated than other disciplines of science in multiple ways.…”
Section: Introductionmentioning
confidence: 99%
“…These translation activities often ignore key differences in study design—i.e., methods and the population of interest (human vs. animal studies)—thus causing confusion and lack of trust when results are conflicting. Our work has shown that government translation of nutrition research (i.e., the Australian Guide to Healthy Eating) fails to capture the attention of young adults as it is not relevant and applicable to their lives, unlike content from SMIs [ 2 ].…”
Section: Introductionmentioning
confidence: 99%